How do different payment schemes to operators affect public transport concessions? A microeconomic model. (July 2020) - Sepúlveda, Juan Pablo; Galilea, Patricia
Abstract: In many large cities worldwide, private companies operate public transport systems under concession contracts granted by the local governments. The performance of these concessions, including the quality of service and amount of subsidy, is often an issue of public debate. In this context, a major factor that determines performance is the concession contract. Payment mechanisms (established in the contract) influence the operator's decisions by providing certain incentives. Therefore, it is important to study the effects of the payment mechanism on the performance of the transport system. In this study, we examine payment schemes that are linear in the frequency of transport services and number of passengers transported; moreover we compare the impact on operators' decisions by incorporating a contract design analysis in the microeconomic modelling. These effects are analysed in terms of operational variables and social welfare, including benefits for reducing externalities. To conduct this analysis, we formulate a microeconomic model and perform numerical simulations. The results show that the payment made per frequency plays an important role in the operator's decision making, that is, the regulator can use this payment as an incentive to modify the service decisions and achieve maximum social welfare. The model also indicates that the per-passenger payment system is an incentive to transport passengers, but after reaching a certain value its increase does not influence the operation of the service. These results may contribute to the discussion on how to design contracts to provide certain incentives. Highlights: We study the payment schemes (PS) to an operator of public transport. The PS have two components: per frequency (PF) and per passengers transported (PP). We analyse the impact of different PS on the operator's decisions. The PF is an incentive to the operator to modify its service decisions. The PP is an incentive to transport passengers, but only until certain value.